Comparative Analysis of Zhongdang Pan And Gerald M. Kosicki's Framing on Covid-19 News in Online Media Kumparan.Com and Beritasatu.Com and Its Recommendations as RPP for Junior High School News Texts - Asmaul Husna, Pesona; Setiawan, Hendra; Meliasanti, Ferina (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The research entitled "Comparative Analysis of Framing Zhongdang Pan and Gerald M. Kosicki on Covid-19 Pandemic News in the Online Media Kumparan.com and Beritasatu.com and Recommendations as a RPP for Junior High School News Texts" aims to find out how online media is framed (in network) kumparan.com and Beritasatu.com in the case of disaster reporting due to the Covid-19 pandemic and to find out the results of Zhongdang Pan and Gerald M. Kosicki's framing analysis of the Covid-19 pandemic that hit Indonesia and the results of the analysis are used as alternative news teaching material in junior high schools. To achieve this goal, researchers studied four framing structures, namely syntactic, script, thematic and rhetorical structures, where these four structures are part of the Zhongdang Pan and Gerald M. Kosicki framing model. There is also an approach and method used in this research, namely a qualitative approach with descriptive methods. From the results of this research, it can be seen that kumparan.com and Beritasatu.com frame it completely, accurately and in accordance with data obtained from reliable sources. In the framing process, kumparan.com and Beritasatu.com do not take sides or support any party. However, if you look at the headlines regarding news in each region in Indonesia, kumparan.com and Beritasatu.com mostly use news titles that focus on government officials or community figures. Then, the results of Zhongdang Pan and Gerald M. Kosicki's framing analysis of the news of the Covid-19 pandemic disaster are also suitable as alternative learning material. In the news text learning materials and research results, researchers can conclude that kumparan.com and Beritasatu.com present news according to facts, even though there are parties that are highlighted, they do not bring down other parties. while maintaining consistent use of language according to linguistic rules in reporting.